Intracerebral haemorrhage: from clinical settings to animal models - Bai, Qian (Stroke Vasc Neurol, 2020)
Spontaneous intracerebral haemorrhage (ICH) is a devastating type of stroke with high mortality and morbidity and for which no effective treatments are available to date. Much experimental and clinical research have been performed to explore its mechanisms regard the subsequent inflammatory cascade and to seek the potential therapeutic strategies. The aim of this review is to discuss insights from clinical settings that have led to the development of numerous animal models of ICH. Some of the current and future challenges for clinicians to understand ICH are also surveyed.